2018
DOI: 10.1259/bjr.20170978
|View full text |Cite
|
Sign up to set email alerts
|

Automatic spectral imaging protocol and iterative reconstruction for radiation dose reduction in typical hepatic hemangioma computed tomography with reduced iodine load: a preliminary study

Abstract: DEsCT with ASIS and ASiR technique can reduce the radiation dose without image quality degradation as compared to the conventional 120-kVp CT. The monochromatic spectral images at 52 keV level with 50% ASiR allows the reduction in total iodine dose without deteriorating diagnostic performance. Advances in knowledge: ASIS combined with ASiR technique, by using monochromatic spectral images at 52 keV level, represents a feasible imaging protocol to reduce the radiation and total iodine dose in assessment of typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…With advances in technology, the radiation exposure dose during the lumbar examination using dual-energy CT with ASiR-V technique is equal to or lower than that with conventional CT (17,18,27). To further validate this, the exposure dosage data for all adults who underwent conventional CT lumbar examinations during July 2018 were retrospectively collected.…”
Section: Ethical Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…With advances in technology, the radiation exposure dose during the lumbar examination using dual-energy CT with ASiR-V technique is equal to or lower than that with conventional CT (17,18,27). To further validate this, the exposure dosage data for all adults who underwent conventional CT lumbar examinations during July 2018 were retrospectively collected.…”
Section: Ethical Statementmentioning
confidence: 99%
“…Like QCT, DECT can also support separate measurements of the BMD of cortical and trabecular bone (5). Notably, the radiation exposure dose of DECT with the volume-based adaptive statistical iterative reconstruction (ASiR-V) technique is equal to or lower than that of conventional CT (17)(18)(19). DECT also has other potential advantages, including detection of bone marrow edema or tumor infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…In some of the studies reviewed [19][20][21][22][23]27,28,34,35,39,40 , a wide range of net iodine doses used in the different tests is described, in milligrams iodine per weight (mgI/kg), from 280 to 600 mgI/kg using SECT equipment, and when performing the same examination with DECT technology, said dose is reduced to a range of 140-510 mgI/kg.…”
Section: Reduction Of the Icm Dose In Dect Equipmentmentioning
confidence: 99%
“…Previous studies have shown that VMS images at approximately 70 keV (range, 67-72 keV) had lower image noise and a higher contrast-to-noise ratio (CNR) than 120-kVp CT images [20,21]. Moreover, the radiation exposure dose of single source dual-energy CT with the volume-based adaptive statistical iterative reconstruction (ASiR-V) technique is equal to or lower than that of conventional CT [22][23][24]. But, reports on the use of radiomics analysis derived from single source dual-energy CT for osteoporosis prediction is still lacking.…”
Section: Introductionmentioning
confidence: 99%